Factionalization of the Majelis Mujahidin Indonesia: Transformation of the Leadership of a Terror Organization into a Political Organization - Yassirly Amrona Rosyada; Alvin Noor Sahab Rizal; Muhammad Noor Sulaiman Syah (Nur Science Institute, 2025)
This study analyzes the Majelis Mujahidin mass organization where in its development there were internal conflicts that caused several internal factions and a shift in leadership figures. Based on the support and study of the theory of factionalism, identity politics, and leadership, this thesis aims to find out some of the factions in the Majelis Mujahidin and the shift in the area of da'wah from Yogyakarta to West Sumatera. This study uses two types of data sources, namely primary data sourced from the field, observation and in-depth interviews. While secondary data is the type of data that comes from scientific works such as books, articles, journals and others related to the context of this research, especially about factionalism and identity politics of the Majelis Mujahidin. While the method in this research is a qualitative-descriptive method that uses a socio-political approach. The results of the study revealed that the Majelis Mujahidin had several factions. The first is the Abu Bakar Ba'asyir faction with a jihadist da'wah style. The two factions of Muhammad Talib where the Majelis Mujahidin in their preaching emphasize study through knowledge. The three factions Irfianda Abidin and Jel Fathullah with political missions. The emergence of Jel Fathullah and Irfianda Abidin advancing in the realm of Indonesian politics is quite surprising for Indonesian Islamic organizations. Both are known to be in the central management structure of the Majelis Mujahidin. As a result, the Majelis Mujahidin, which is well-known as an organization that challenges the democratic system, raises its figures to participate in the contestation in a system that it considers kufr. The emergence of political factions in the Majelis Mujahidin certainly shows that their existence is quite massive to this day. REFERENCES Abdul Aziz, “Gerakan Politik Penegakan Syari’at Islam Di Era Reformasi Kasus Majelis Mujahidin Indonesia 2000-2005”, dalam Jurnal Review Politik 2, no. 2, 2012. Abi Chusna, “Konsep Jihad Hizbut Tahrir Indonesia (HTI) dan Majelis Mujahidin Indonesia (MMI): Studi Perbandingan,” Disertasi UIN Sunan Ampel Surabaya, 2014. Ali Sodiqin, “Genealogi Gerakan Penegakan Syari’at Islam Di Indonesia”, dalam Al-Mazahib: Jurnal Pemikiran Hukum 3, no. 1, 2015. Asran Jalal, A. J.